2015
DOI: 10.1007/s00592-015-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and cognitive function in patients with type 2 diabetes: an 8-year prospective observational study

Abstract: word count: 200

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
3
22
0
1
Order By: Relevance
“…There was a high risk of GAD among patients with a long duration (4 9 years) of T2DM, which is consistent with reports that a long duration of DM is associated with a high risk of AD and with worsening anxiety symptoms. 27,28 Of the T2DM patients in this study, those with the highest GAD risk had comorbid depressive disorder, which is consistent with the literature. 28 Another study reported that MDD patients and GAD patients often exhibit symptoms of both disorders simultaneously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was a high risk of GAD among patients with a long duration (4 9 years) of T2DM, which is consistent with reports that a long duration of DM is associated with a high risk of AD and with worsening anxiety symptoms. 27,28 Of the T2DM patients in this study, those with the highest GAD risk had comorbid depressive disorder, which is consistent with the literature. 28 Another study reported that MDD patients and GAD patients often exhibit symptoms of both disorders simultaneously.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies of T2DM patients have focused on the prevalence of anxiety symptoms or AD, rather than on GAD. 11,[17][18][19][20][21][27][28][29][30][31][32] Another unique feature of this study is that it analyzed a specific Asian population (i.e., ethnic Han Chinese). Table 1 shows that, compared to GAD patients in the GP, T2DM GAD patients were more likely to have high CCI scores, be older, female, and have multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the recent prospective observational study demonstrating that a lower education level at baseline was associated with significantly higher depression scores among individuals with diabetes [32]. Thus, combining all of our earlier results, we recommend that subjects newly diagnosed with diabetes should be screened for depression and that specific interventions for depression should be provided, especially for those with less education.…”
Section: Discussionsupporting
confidence: 91%
“…These data indicate that screening for and management of anxiety symptoms in diabetes, particularly in those with suboptimal diabetes management, chronic complications and depression, may be beneficial. Current recommendations are to screen and consider therapies for anxiety at key points in the course of type 2 diabetes, including diagnosis, onset of complications and commencement of insulin [11,26]. The most important finding in this study is that, for a group of individuals with long duration disease and chronic complications (median diabetes duration of 8.9 years in group 2), less severe anxiety symptoms were more prevalent and persistent than previously recorded and displayed a lifetime course.…”
Section: Discussionmentioning
confidence: 50%
“…By assessing anxiety symptoms over 4 years, we found that a substantially larger proportion (12.6%) continued to experience subthreshold anxiety symptoms that waned but remained higher than those with low-no anxiety. One explanation for this finding is that GAD presents as residual anxiety symptoms that recur over time, displaying the pattern of relapse and remission observed in the general population [12,26]. Thus, a single assessment and relying on DSM-IV GAD criteria may underestimate the impact of psychological issues in people with diabetes.…”
Section: Discussionmentioning
confidence: 99%